The B chromosome of the grasshopper Abracris flavolineata: from populational analysis to cytogenomics - Cabral de Mello, Diogo Cavalcanti (Semina: Ciências Biológicas e da Saúde, 2018)
B chromosomes occur in addition to normal chromosome complement (A complement) in about 15% of Eukaryotes. For Orthoptera they were noticed in about 190 species with prevalence in the superfamily Acridoidea (14.6%), which is considered a "hot spot" for B chromosome emergence. One of these Acridoidea species is Abracris flavolineata (Ommatolampidinae), a South American grasshopper that harbor one or two submetacentric B chromosomes. The main difference for this species in comparison to most other B chromosomes is that in A. flavolineata the B chromosome is not enriched of heterochromatin. In this way we have to explore this species as model to understand composition, evolution and possible transcriptional activity of B chromosomes. In this talk the evolutionary history of A. flavolineata B chromosome will be presented from geographical and temporal population analysis to cytogenetic point to view. These histories are based in obtaining of integrated data, like chromosomal analysis, molecular studies, high-throughput DNA sequencing and imunocytogenetics that revealed interesting picture concerning B chromosome evolution.